2021
DOI: 10.1371/journal.pone.0255080
|View full text |Cite
|
Sign up to set email alerts
|

Family planning in Pacific Island Countries and Territories (PICTs): A scoping review

Abstract: The use of contraceptives for family planning improves women’s lives and may prevent maternal deaths. However, many women in low and middle-income countries, including the Pacific region, still die from pregnancy-related complications. While most health centres offer family planning services with some basic contraceptive methods, many people do not access these services. More than 60% of women who would like to avoid or delay their pregnancies are unable to do so. This scoping review identifies and analyses ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
0
9
0
4
Order By: Relevance
“…In PICTs, more research is required to understand the drivers of young adults’ health-seeking behaviour, access to SRH information and services, types of SRH services accessed, and unmet need for services [ 1 ]. Evidence from this scoping review shows that there are limited data available on the health-seeking behaviour of young adults in PICTs, perhaps because of the sensitivities around socio-cultural expectation and premarital sexual behaviour [ 4 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PICTs, more research is required to understand the drivers of young adults’ health-seeking behaviour, access to SRH information and services, types of SRH services accessed, and unmet need for services [ 1 ]. Evidence from this scoping review shows that there are limited data available on the health-seeking behaviour of young adults in PICTs, perhaps because of the sensitivities around socio-cultural expectation and premarital sexual behaviour [ 4 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Timely access to sexual and reproductive health (SRH) information and services by young adults in Pacific Island Countries and Territories (PICTs) remain low despite the availability of SRH services [ 1 ]. Globally, young adulthood is a critical time of development where many opportunities and challenges exist.…”
Section: Introductionmentioning
confidence: 99%
“…32 Stage 1: identifying the research question The research question was identified as a result of our research on women's sexual and reproductive health in the Pacific. [37][38][39] Using an iterative process, our study team identified a broad research question defining the target population, concept and context to guide the focus, scope and intent of the review. 33 36 In conducting this scoping review, our research question is: What are women's experiences of menopause in LIC and MIC in the Asia Pacific?…”
Section: Methods and Analysismentioning
confidence: 99%
“…The research question was identified as a result of our research on women’s sexual and reproductive health in the Pacific 37–39. Using an iterative process, our study team identified a broad research question defining the target population, concept and context to guide the focus, scope and intent of the review 33 36.…”
Section: Methods and Analysismentioning
confidence: 99%
“…These include: international organisations, donor agencies, NGOs, civil society organisations (CSOs), participatory research programmes based at universities and independent research organisations, unions, faith-linked groups and informal women’s collectives and coalitions. Outreach programmes can also be delivered in ‘settings’ such as “schools, villages, workplaces, churches, radio talk-back shows …” ([ 44 ], p.21). Researchers investigating the role of gender in Zika prevention behaviours in the Dominican Republic raised an essential issue for reducing the burden of Zika and other similar mosquito-borne diseases (i.e.…”
Section: Recommendationsmentioning
confidence: 99%